Impact of Ionic Liquids on Induction of Wheat Microspore Embryogenesis and Plant Regeneration - Dorota Weigt; Idzi Siatkowski; Magdalena Magaj; Agnieszka Tomkowiak; Jerzy Nawracała (Agronomy, 2020)
Ionic liquids are novel compounds with unique chemical and physical properties. They can be received based on synthetic auxins like 2,4-dichlorophenoxyacetic acid or dicamba, which are commonly used hormones in microspore embryogenesis. Nevertheless, ionic liquids have not been adapted in plant in vitro culture thus far. Therefore, we studied the impact of ionic liquids on the ability to undergo microspore embryogenesis in anther cultures of wheat. Two embryogenic and two recalcitrant genotypes were used for this study. Ten combinations of ionic liquids and 2,4-dichlorophenoxyacetic acid were added to the induction medium. In most cases, they stimulated induction of microspore embryogenesis and green plant regeneration more than a control medium supplemented with only 2,4-dichlorophenoxyacetic acid. Two treatments were the most favorable, resulting in over two times greater efficiency of microspore embryogenesis induction in comparison to the control. The effect of breaking down the genotype recalcitrance (manifested by green plant formation) was observed under the influence of 5 ionic liquids treatments. Summing up, ionic liquids had a positive impact on microspore embryogenesis induction and green plant regeneration, increasing the efficiency of these phenomena in both embryogenic and recalcitrant genotypes. Herbicidal ionic liquids can be successfully used in in vitro cultures.